2023
DOI: 10.1136/bmj-2022-074520
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality after low dose exposure to ionising radiation in workers in France, the United Kingdom, and the United States (INWORKS): cohort study

David B Richardson,
Klervi Leuraud,
Dominique Laurier
et al.

Abstract: Objective To evaluate the effect of protracted low dose, low dose rate exposure to ionising radiation on the risk of cancer. Design Multinational cohort study. Setting Cohorts of workers in the nuclear industry in France, the UK, and the US included in a major update to the International Nuclear Workers Study (INWORKS). Participants 309 932 workers with individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 77 publications
0
40
0
Order By: Relevance
“…Empirically, several pertinent studies have been published subsequent to UNSCEAR Report 2012, and were thus not taken into account in the IAEA Report. These include new results from the LSS [5], the INWORKS study of nuclear workers [6,7], a pooled analysis of studies on leukaemia after low-dose exposure [8], the EPI-CT study on cancer after computed tomography exams during childhood [9,10], and the PUMA study based on pooled cohorts of miners exposed to Radon and its progeny [11]. These studies set up cohorts with up to hundreds of thousands of participants accruing millions of person-years of follow-up.…”
Section: Reviewmentioning
confidence: 99%
“…Empirically, several pertinent studies have been published subsequent to UNSCEAR Report 2012, and were thus not taken into account in the IAEA Report. These include new results from the LSS [5], the INWORKS study of nuclear workers [6,7], a pooled analysis of studies on leukaemia after low-dose exposure [8], the EPI-CT study on cancer after computed tomography exams during childhood [9,10], and the PUMA study based on pooled cohorts of miners exposed to Radon and its progeny [11]. These studies set up cohorts with up to hundreds of thousands of participants accruing millions of person-years of follow-up.…”
Section: Reviewmentioning
confidence: 99%
“…Exposure to radiation is hazardous to health, even at low levels (Beyea, 2012;National Research Council, 2006). Therefore, when people come into contact with these wastes, they are at higher risk of developing cancers and a range of other health effects (Little et al, 2023;Richardson et al, 2023). A particular complication is that some of these radioactive substances have extremely long half-lives, and remain hazardous for hundreds of thousands of years.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, the US study found that the risk estimates were significantly greater for those 56% of workers first hired in 1960 or later in comparison with the full cohort of 101 363 workers, for all solid cancers combined and for certain individual site-specific solid cancers, such as lung, colon, and pleural cancer. A combined analysis of mortality data for 309 932 workers from the UK, the USA and France in the recent International Nuclear Workers Study (INWORKS) [4] also found higher risks for solid cancers among those 77% of workers first hired after 1957 and even more so among those 61% first hired after 1964.…”
Section: Introductionmentioning
confidence: 99%